Cellulose Nanocrystals With Enhanced Thermal Stability Reinforced Thermoplastic Polyurethane - Khairatun Najwa, Mohd Amin; Annamalai, Pratheep Kumar; Martin, Darren (Malaysian Analytical Sciences Society, 2017)
Melt compounding processing approach for incorporating cellulose nanocrystals (CNC) into thermoplastic polyurethane (TPU) has not well been explored. This is primarily due to the poor thermal stability and dispersibility of CNCs. As they are typically obtained from sulphuric acid hydrolysis, they give rise to degradation and discolouration of the extruded nanocomposites. The investigation of this research demonstrates sulphuric acid hydrolysis (CNC-S), phosphoric acid hydrolysis (CNC-P) and a novel non-hydrolytic high energy bead milling method (CNC-MC) into a polyether based thermoplastic polyurethane via melt compounding using twin screw extruder. The TPU film incorporated with CNC-S obviously shows the sign of CNC degradation where TPU film was changed to brown colour. The tensile strength of TPU reinforced with CNC-S, CNC-P and CNC-MC shows 18%, 16% and 14% of improvement at CNC loading of 0 to 1 wt.% upon host polymer. CNCs isolated via mild acid hydrolysis and mechanical milling methods, can be easily processed via large scale melt-processing techniques for reinforcing thermoplastic polyurethane without affecting their physical appearance and elastic properties.